Long-term population trends and shifts in distribution of Bewickâ€™s Swans Cygnus columbianus bewickii wintering in northwest Europe - Beekman, Jan; Koffijberg, Kees; Wahl, Johannes; Kowallik, Christine; Hall, Colette; Devos, Koen; Clausen, Preben; Hornman, Menno; Laubek, Bjarke; LuigujÃµe, Leho; et al. (Wildfowl, 2019)
Coordinated international censuses of the Northwest European Bewickâ€™s SwanÂ Cygnus columbianus bewickii population have been undertaken across the swansâ€™ wintering range at c. 5-year intervals since 1984. During the early years of the study, numbers increased steadily to a peak of 29,780 individuals in January 1995, but then declined by 39.4% to 18,057 swans counted in January 2010 before showing a partial recovery to 20,149 recorded in January 2015. Changes in distribution across the wintering range were also recorded; a higher proportion of the population now remains in more easterly countries (notably Germany) in mid-winter, whilst only a handful of birds migrated to Ireland (at the western edge of the range) during the 2000s compared to >1,000 wintering there at the start of the study. Variation between censuses in the proportion of swans recorded in different parts of the range were attributable to weather conditions, with more swans wintering further north in warmer years. The overall percentage of cygnets recorded in each of the census years ranged from 9.6% in 2010 to 13.2% in 2005, with no obvious consistency over time in the distribution of cygnets across the wintering range. There were however changes between 1990 and 2015 in the swansâ€™ use of feeding habitats, with a decline in the proportion of birds on pasture and a corresponding increase in those on arable land. Decreases in the total population size and changes in distribution in the 21st century have implications for the designation and resultant protection of sites of international importance for the species.